Serum Salusin Levels in ST-Segment Elevation Myocardial Infarction - Yilmaz, Mustafa; Atescelik, Metin; Ardic, Sukru; Goktekin, Mehmet C.; Yildiz, Mustafa; Gurger, Mehtap; Ilhan, Nevin (Clin Lab Publ, 2016)
Background: In our study, we aimed to determine the change in levels of salusin-alpha and salusin-beta at admission and after the treatment in patients with STEW, who have active atherosclerosis. Methods: Serum salusin-alpha and beta levels of 50 patients diagnosed with STEMI in the emergency department were measured at admission and on 7th day post-treatment and compared with serum salusin levels of 50 healthy volunteers. Results: In STEMI patients, salusin-alpha levels were found to be significantly decreased (p < 0.001) and salusin-beta levels were found to be significantly increased (p < 0.001) compared to healthy volunteers in the control group. 7th day post-treatment salusin-alpha levels were found to be lower and salusin-beta levels were found to be at a higher level compared to healthy individuals (p < 0.001). Negative correlation (r = -.322 p = 0.023) was found between salusin-alpha levels and pulse rate. But no significant correlation was found between salusin-beta levels and biochemical parameters. Conclusions: The data of this study support the fact that salusin-alpha levels decrease and salusin-beta levels increase in acute cases such as STEMI.
Keywords: emergency department; salusin alpha; salusin beta; ST elevation myocardial infarction